The Development of E-Module to Improve Learning Results Introduction to Accounting I - Togi Martua Damanik; Saidun Hutasuhut; Fitrawaty Fitrawaty (BIRCU, 2020)
To realize the success of improving education, efforts must be made from various sides, namely paying attention to all components that play an important role such as improving the quality of lecturers, curriculum, facilities and infrastructure, management and community participation. E-module with the sigil application really helps students in lectures because the tutorial content facility supports both descriptions in text, images, and videos so that students have an interest, are able to understand and review learning materials properly and motivate them to study independently. The objectives of this study are: 1) to produce problem solving-based e-modules that are suitable for use in learning, 2) to determine the effectiveness of e-modules developed in improving learning outcomes. Introduction to accounting I. This type of development research uses the Borg & Gahl model with the Dick n Carey development model. The results showed; (1) The instructional media expert test is at very feasible criteria (80.26%), (2) the learning design expert test is in the appropriate criteria (75%), (3) the material expert test is at very feasible criteria (92.5 %), (4) small group trials are in very feasible criteria (84.16%) (5) Limited field trials are in very feasible criteria (81.79%). Based on the results of the feasibility assessment of the developed problem solving-based e-module with the percentage of the average score of the overall variable score of 82.74%, it is included in the “very feasible” category, meaning that the developed e-module is proven to be feasible for use.